Optimal bit selection for large-diameter wellbore drilling in an ultra-deep well - Lili CHEN; Wenzhe LI; Jianhua GUO; Ke LI; Zhixiang CAI; Jie WU; Weining XU; Xiaohua ZHU (Petroleum Exploration and Development, 2025)
To optimize the bit selection for large-diameter wellbore in the upper section of an ultra-deep well S-1, a full-well dynamic model integrating drill string vibration and bit rock-breaking was established and then verified using measured vibration data of drilling tools and actual rate of penetration (ROP) from Well HT-1 in northern Sichuan Basin. This model was employed to calculate and analyze drill string dynamic characteristics during large-diameter wellbore drilling in the Jurassic Penglaizhen Formation of Well S-1, followed by bit optimization. Research results show that during the drilling in Penglaizhen Formation of Well S-1, considering both the ROP of six candidate bits and the lateral/axial/torsional vibration characteristics of downhole tools, the six-blade dual-row cutter bit with the fastest ROP (average 7.12 m/h) was optimally selected. When using this bit, the downhole tool vibration levels remained at medium-low values. Field data showed over 90% consistency between actual ROP data and dynamic model calculation results after bit placement, demonstrating that the model can be used for bit program screening.